Pengembangan Higher Orther Thinking Skills Siswa Menggunakan Desain Pembelajaran Kreatif-Produktif pada Pelajaran Biologi SMAKelas XI di Kabupaten Banyumas - Julianto1, Teguh; Husin1, Arief; Pujiastuti2, Ferry; Andriani3, Yulina; Sulistyawati4, Ida (Universitas Sebelas Maret, 2018)
The selection of proper learning design can determine the studentâ€™s achievement of High Order Thinking Skills(HOTS). The development of creative-productive learning design becomes one of the strategies to achieve students' HOTS skill. Students were facilitated and given the responsibility to be able to develop HOTS skills effectively. Students are taught to doing science-based learning activities in various ways such as observation, discussion, or experiment, and trained to be creative and productive in interpreting natural phenomenon. The purpose of this research was to develop the creative-productive learning design as a strategy to improve students' HOTS skills in biology learning. This research used Quasi-experimental design Â with the population of XI grade student of Senior High School in Banyumas Regency. The students' HOTS skills that being developed include student skills in observing objects, analyzing, identifying, explaining, and communicating the results of their learning activities. The results of this research shows that creative-productive learning design can develop high-level thinking skills (HOTS) of students with varying degrees of achievement